Effect of current profile and epoxy potlife on surface resistivity of electrodeposited epoxy coating - Nik Ab Rashid, Nik Ahmad Luqmanul Hakim (2024)
Electrodeposition (EPD) is a widely utilized method for applying epoxy coatings due to its ability to precisely control coating thickness and uniformity, essential for consistent performance in various applications. This study examines the impact of current-voltage profiles on the surface resistivity of electrodeposited epoxy coatings, which are critical for applications such as electrical insulation, electronics packaging, and corrosion prevention. Despite their significance, the precise correlations between electrodeposition parameters and surface resistivity have not been fully established. We investigated this relationship using characterization techniques like the Four-Point Probe method, Ultraviolet-Visible (UV-Vis) Spectrophotometry, and Field Emission Scanning Electron Microscopy (FESEM), alongside a design of experiments (DOE) approach employing Central Composite Design (CCD) in the Response Surface Methodology (RSM) framework. Results indicated that the current-voltage profile significantly influences surface resistivity, with optimal profiles achieving a coating thickness of 153.26 μm at 60V and 1-hour pot life, and resistivity values of 758.2 kΩ-cm/□ at 30V, 798.2 kΩ-cm/□ at 40V, and 818.0 kΩ-cm/□ at 60V for 1-hour pot life. RSM analyses confirmed significant effects of pot life and voltage on thickness and resistivity. These findings are crucial for industries relying on epoxy coatings for electrical insulation, electronics packaging, and corrosion prevention, as they can achieve improved performance and reliability by adopting the optimal current-voltage profiles identified. This study advances understanding of the relationship between current-voltage profiles and surface resistivity of electrodeposited epoxy coatings, paving the way for materials with customized resistivity properties.